Peningkatan UMKM eMKa CCTV Melalui Digital Marketing Berbasis Web - Lisya, Rahma; Saiful, Saiful; Putra, Fabian Anugrah Putra; Nabilla Dwi Puspita; Novadilastri, Novadilastri; Sularno, Sularno (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2023)
The use of the website has become a concern by many circles, so making companies and government agencies use the company's website. In this century every company must complete its means of communication by creating a website. And also as a transaction function because it can connect to the company, a company must continue to show their quality in selling products / Please note that business competition is currently very tight and each company / service in the company is reasonable. Currently, customers of eMKa CCTV start from individuals and companies. Some companies include PT Suka Fajar.